Mycobacterium tuberculosis-Specific IL-21(+)IFN-γ(+)CD4(+) T Cells Are Regulated by IL-12 - Li, Li (PLoS One, 2016)
In the current study of Mycobacterium tuberculosis (MTB)-specific T and B cells, we found that MTB-specific peptides from early secreted antigenic target-6 (ESAT-6) and culture filtrate protein-10 (CFP-10) induced the expression of IL-21 predominantly in CD4(+) T cells. A fraction of IL-21-expressing CD4(+) T cells simultaneously expressed Th1 cytokines but did not secrete Th2 or Th17 cytokines, suggesting that MTB-specific IL-21-expressing CD4(+) T cells were different from Th1, Th2 and Th17 subpopulations. The majority of MTB-specific IL-21-expressing CD4(+) T cells co-expressed IFN-γ and IL-21(+)IFN-γ(+)CD4(+) T cells exhibited obviously polyfunctionality. In addition, MTB-specific IL-21-expressing CD4(+) T cells displayed a CD45RO(+)CD62L(low)CCR7(low)CD40L(high)ICOS(high) phenotype. Bcl-6-expression was significantly higher in IL-21-expressing CD4(+) T cells than IL-21(-)CD4(+) T cells. Moreover, IL-12 could up-regulate MTB-specific IL-21 expression, especially the frequency of IL-21(+)IFN-γ(+)CD4(+) T cells. Taken together, our results demonstrated that MTB-specific IL-21(+)IFN-γ(+)CD4(+) T cells from local sites of tuberculosis (TB) infection could be enhanced by IL-12, which have the features of both Tfh and Th1 cells and may have an important role in local immune responses against TB infection.